Super (a,d)-Edge-antimagic Total Labeling of Shakle of Fan Graph - Vikade, Wicha Dwi; Dafik, Dafik (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
A graph G of order p and size q is called an it (a,d)-edge-antimagic total if there exist a bijection f : V(G)cup E(G) o 1,2,dots,p+q such that the edge-weights, w(uv)=f(u)+f(v)+f(uv), uv in E(G), form an arithmetic sequencewith first term a and common difference d. Such a graph G is called it super if the smallest possible labels appear on the vertices. In this paper we study super (a,d)-edge-antimagic total properties of connectedÂ of amalgamation of Fan Graph. The result shows that amalgamation of Fan Graph admit a super edge antimagic total labeling for din0,1,2 for n geq 1. It can be concluded that the result of this research has convered all the feasible n, d.